Enteropeptidase inhibition improves kidney function in a rat model of diabetic kidney disease. Issue 1 (6th October 2020) - Sugama, Jun; Katayama, Yuko; Moritoh, Yusuke; Watanabe, Masanori
Abstract: Aim: To examine the effects of an enteropeptidase inhibitor, SCO‐792, on kidney function in rats. Materials and Methods: The pharmacological effects of SCO‐792 were evaluated in Wistar fatty (WF) rats, a rat model of diabetic kidney disease (DKD). Results: Oral administration of SCO‐792 increased faecal protein content and improved glycaemic control in WF rats. SCO‐792 elicited a rapid decrease in urine albumin‐to‐creatinine ratio (UACR). SCO‐792 also normalized glomerular hyperfiltration and decreased fibrosis, inflammation and tubular injury markers in the kidneys. However, pioglitazone‐induced glycaemic improvement had no effect on kidney variables. Dietary supplementation of amino acids (AAs), which bypass the action of enteropeptidase inhibition, mitigated the effect of SCO‐792 on UACR reduction, suggesting a pivotal role for enteropeptidase. Furthermore, autophagy activity in the glomerulus, which is impaired in DKD, was elevated in SCO‐792‐treated rats. Finally, a therapeutically additive effect on UACR reduction was observed with a combination of SCO‐792 with irbesartan, an angiotensin II receptor blocker. Conclusions: This study is the first to demonstrate that enteropeptidase inhibition is effective in improving disease conditions in DKD. SCO‐792‐induced therapeutic efficacy is likely to be independent of glycaemic control and mediated by the regulation of AAs and autophagy. Taken together with a combination effect of irbesartan, SCO‐792 may be a novel therapeutic option for patients with DKD.